Visiones externas sobre el INVI - Ramírez, Ronaldo; Pelli, Víctor Saúl; Lentini, Mercedes; Rodríguez, Alfredo; Sugranyes, Ana; Raposo, Alfonso; Sahady Villanueva, Antonio (Revista INVI, 2016)
Visiones externas sobre el INVI